Potensi Sumber Daya Alam Desa Hargomulyo - Lukisworo, Agustinus Aryo (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
As part of the implementation of KKN Periode 79 Universitas Atma Jaya Yogyakarta, Kelompok 1 (FirstGroup) of Unit A was placed in Hargomulyo Village, Kokap, Kulon Progo, Daerah Istimewa Yogyakarta. In regards with the Covid-19 pandemic, all KKN activities were carried out in online mode. Therefore all of KKN program proposed by this Group are based on secondary data obtained from online inquiries. The findings show that Hargomulyo Village has various potentials, ranging from entrepreneurial, agricultural, tourism, to cultural. Among the potential that exists in Hargomulyo Village, this Group focuses on the development one of Kulon Progo’s tradisional foods, namely growol. Based on the observations made by the 1st Group, the production and distribution of growol decreased from time to time. In order to preserve to exitence of growol and increasing the distribution of this food more widely, this Group proposed growol marketing development idea through a digital platform. It is hoped that the development of growol marketing, besides being able to maintain the existence of growol as a traditional food, can also support the economic development of Hargomulyo Village.